1997
DOI: 10.1111/j.1600-0471.1997.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Geography and Human Settlements in Ancient Southern Arabia

Abstract: The use of remote sensing in archaeological research leads to a better understanding of the geography of ancient and modern South Arabia. The five main regions are discussed in relation to the conditions for settlement and farming. A case study from the heartland of the Kingdom of Awsān indicates in the lower part of Wādī Marha beginning of irrigation in the second half of the third millenium and an end already in the first half of the first millenium BC. The huge tell of Haǧar Yahirr seems to have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Data are even more elusive in Yemen. The large oasis of Mareb and its sophisticated irrigation system was probably developed during this period (Wagner, 1993) and the same is accepted for the Wadi Markha to the south (Brünner, 1997). These dates are still a matter of discussion.…”
Section: The Littoral Of the Indian Ocean: The Mangrove Of Suwayhmentioning
confidence: 80%
“…Data are even more elusive in Yemen. The large oasis of Mareb and its sophisticated irrigation system was probably developed during this period (Wagner, 1993) and the same is accepted for the Wadi Markha to the south (Brünner, 1997). These dates are still a matter of discussion.…”
Section: The Littoral Of the Indian Ocean: The Mangrove Of Suwayhmentioning
confidence: 80%
“…Though Southwest Arabia remains one of the least archaeologically known areas of the Near East, a comparative wealth of research documents the importance of irrigation among ancient states and their precursors (e.g., Brunner 1997Brunner , 2000Brunner and Haefner 1986;Coque-Delhuille 1998;Francaviglia 2002;Gentelle 1991;Gentelle and Coque-Delhuille 1998;Hehmeyer 1989;Mouton 2004;Vogt 2004;Vogt, Buffa, and Brunner 2002), and recent investigations have begun to establish the tandem beginnings of crop agriculture and irrigation during the fourth millennium BC 1 (see Edens 2005; Edens and Wilkinson 1998). Italian research in Khawlan identified ceramic impressions that include wheat, barley, and sorghum dated to the latter half of the third millennium (Costantini 1990).…”
Section: Early Evidence Of Crops and Irrigationmentioning
confidence: 99%
“…In ancient times many irrigation oases were established at the south-western margin of the Ar-Rub' Al-Khali (Brunner, 1997). The main reason for this development was low precipitation and increasing population in Sabaean times.…”
Section: Introductionmentioning
confidence: 98%